2022
DOI: 10.3389/fpsyt.2022.855016
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among patients with chronic non-communicable diseases during COVID-19 pandemic in Southern Ethiopia: A cross-sectional analytical study

Abstract: BackgroundThe COVID-19 outbreak became a continuing global health agenda. It has a significant impact on individuals’ quality of life (QOL). Patients with preexisting medical conditions may have severely reduced QOL. The aim of this study was to assess QOL and its associated factors among patients with chronic non-communicable diseases (NCDs) during COVID-19 pandemic at Sidama Regional State, southern Ethiopia.MethodsWe conducted a multicenter, cross-sectional study from 1 June to 1 September 2021. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 53 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…The results of this review revealed the presence of a clear relationship between the COVID-19 pandemic, mental health, and risk and protective factors for NCDs. Several studies identified a significant association between increased substance use and increased levels of anxiety and depression [36,37,41,44]. Similar associations were found between missed medical appointment and sedentary lifestyle and, poor treatment control and sedentary lifestyles, physical inactivity and substance use, and poor health-seeking behavior and substance use [25,26,27].…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…The results of this review revealed the presence of a clear relationship between the COVID-19 pandemic, mental health, and risk and protective factors for NCDs. Several studies identified a significant association between increased substance use and increased levels of anxiety and depression [36,37,41,44]. Similar associations were found between missed medical appointment and sedentary lifestyle and, poor treatment control and sedentary lifestyles, physical inactivity and substance use, and poor health-seeking behavior and substance use [25,26,27].…”
Section: Resultsmentioning
confidence: 84%
“…Among this, 14 studies focused on chronic disease patients, five focused on diabetes, three focused on hypertension, two focused on diseases and/ or hypertension, one focused on cancer, and one focused on cardiovascular disease. The review findings were organized into five frequently reported themes and subthemes: these are 1) disruption of follow-up care and poor health care utilization reported by 11 studies [10,11, 23,24,25,26,27,28,29,30,31]; 2) increased anxiety, stress, depression, and increased mental health problems reported by eight studies [15,32, 34,35,37,38,39,43]; 3) substance use reported by four studies [36,37,41,44]; 4) decreased physical activity and sedentary life reported by three studies [33,36,44]; and 5) increased food insecurity and poor dietary habits due to COVID-19 among NCDs patients, reported in five studies [36,40,42,43,44] Studies included in this review did not focus on the same subject matter. Some studies focused on one theme and others focus on more than two themes; for instance, (Andualem et al, 2020) examined adherence to lifestyle modifications and reported on diet, exercise, smoking, and alcohol, whereas (Abate et al, 2022) examined adherence to physical exercise recommendations and reported only on exercise compliance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations